Host plant resistance, foliar insecticide application and natural enemies play a role in the management of Melanaphis sorghi (Hemiptera: Aphididae) in grain sorghum - Uyi, Osariyekemwen; Lahiri, Sriyanka; Ni, Xinzhi; Buntin, David; Jacobson, Alana; Reay-Jones, Francis P. F.; Punnuri, Somashekhar; Huseth, Anders S.; Toews, Michael D. (Frontiers in Plant Science, 2022)
The invasive Melanaphis sorghi (Theobald) (=Melanaphis sacchari Zehntner) is a serious pest of sorghum production in the southern USA. Demonstration of technologies that provide effective control is key to management of this pest. Here, we investigated the effect of host plant resistance (resistant cultivar: DKS37-07 and susceptible cultivar: DKS53-53) and a single foliar insecticide (flupyradifurone: Sivanto Prime) application on M. sorghi infestations and the role of natural enemy populations in grain sorghum production across five locations in four states in southeastern USA. Foliar insecticide application significantly suppressed M. sorghi infestations on both the resistant and susceptible sorghum cultivars across all locations. Planting host plant resistant cultivar (DKS37-07) significantly reduced aphid infestation across all locations. Plant damage ratings did not vary widely, but there was generally a positive association between aphid counts and observed plant damage, suggesting that increasing aphid numbers resulted in corresponding increase in plant damage. Planting host plant resistance cultivar foliar and insecticide application generally preserved grain yield. Both sorghum hybrids supported an array of different life stages of natural enemies (predators [lady beetle larvae and adults; hoverfly larvae and lacewing larvae] and parasitoids [a braconid and aphelinid]) for both the sprayed and non-sprayed treatments. We found a strong and significant positive relationship between the natural enemies and the M. sorghi infestation. Results suggest that planting host plant resistance cultivar and the integration of natural enemies with insecticide control methods in the management of M. sorghi is central to the development of an effective pest management strategy against this invasive pest.